2012
DOI: 10.1111/j.1757-7861.2011.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of lordosis and disk height after single‐level transforaminal lumbar interbody fusion

Abstract: Intervertebral height and lumbar lordosis reconstruction are important for achieving good surgical results; guidance regarding the likely changes in lumbar lordosis and disk height after TLIF is provided by our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 22 publications
0
64
3
2
Order By: Relevance
“…According to the change of SS, the ideal LL should increase. Kepler et al [43] evaluated the surgical outcome with a visual analog scale; they found the patients with low LL had more probability to suffer low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…According to the change of SS, the ideal LL should increase. Kepler et al [43] evaluated the surgical outcome with a visual analog scale; they found the patients with low LL had more probability to suffer low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Posterolateral placement within the intervertebral space, where the endplate is thicker [8] and stronger [8,26], has been suggested following a biomechanical study assessing the risk of cage subsidence [14], whereas central placement has shown greater subsidence in a clinical study [15]. With regard to anterior placement, both a cadaveric [27] and a clinical study [28] involving TLIF found no difference in intervertebral lordosis when cages were placed in the anterior half of the disc space. However, the surgical technique in both studies did not involve bilateral total facetectomies and excision of adjacent spinous processes, nor did they aim for extreme anterior placement, so this may have limited the final lordosis achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Complications assessed include infection, pseudarthrosis, hardware-related complications and graft donor site morbidities. Clinical outcomes were assessed based on a 4-grade system: excellent, good, satisfactory and poor, in accordance with the modified Odom's criteria [21].…”
Section: Methodsmentioning
confidence: 99%